Promoting Participatory Budgeting Practices in Indonesia: Lessons from Malang City - Aditya Wisnu Pradana (Policy & Governance Review, 2022)
This study aims to analyze community participation in the process of development planning and APBD formulation in Malang City. This research uses a qualitative approach and the data is sourced from document studies, literature studies and in-depth interviews with informants selected by a purposive method. The results show that even though the process of dialogues in the implementation of Musrenbang RKPD has been well involving various elements of society in order to plan the development of the regions, the final decision remains dominant in the government hands. Moreover, the spaces of community participation in the post-musrenbang stage are also known to be inadequate. There are four factors hampering the community participation: low political commitments of the government elites, not yet optimal channels of the community participation, less supportive government bureaucrats, and lack of public awareness. There are four strategic efforts to strengthen the community participation: provide political education to civil society, implement the community aspiration ceiling in the Musrenbang RKPD, form the community forum in the post-musrenbang stage, and implement a public planning and budgeting system that supports the principles of good governance.